RETROSPECTIVE OF TREATMENT FORMS AGAINST ANDROGENIC ALOPECIA - Regina Portes Abrahão, Thayz; Pires Bispo Andrade, Raquel; Portes Abrahão, Danilo; Cristina Ribas, Carolina; Caroline Ferreira Passos da Silva, Luciana; Moura Tomitan, Mariana; Barbosa de Assis, Daniela; Silva Brito, Ingrid; Mendes de Oliveira , Sara; Barbosa, Oliveira; Gisell Velázquez Gómez , Andrea (Health and Society, 2025)
Androgenic Alopecia is a pathology that affects a significant percentage of the population. The search for forms of treatment arises from the need for acceptance or to achieve the beauty standards required in society, whether as a definitive or temporary treatment. This is a retrospective through the analysis of digitally collected data on the development of forms of treatment against androgenic alopecia. Using a basic, descriptive research, carried out using bibliographic and documentary data. The longitudinal research on the development of techniques and the use of published methods, aims at delineating the treatment against AGA.